Penerapan Sikap Kedisiplinan Anak Sejak Dini Dalam Meningkatkan Perkembangan Sosial Anak di TK Plus Usman Al-Farsy Pademawu Pamekasan - Normasitoh Normasitoh; Sitti Romlah (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the implementation of discipline among children from an early age, the role of teachers in instilling discipline, and the impact on children's social development at TK Plus Usman Al-Farsy, Pademawu, Pamekasan. The study employs a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. Research informants included the school principal, teachers, and students' parents. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results indicate that discipline is instilled through habitual practices integrated into all school activities—such as arriving on time, lining up, praying, performing congregational Dluha prayers, queuing, maintaining cleanliness, and tidying up learning materials. Teachers act as role models, guides, motivators, and supervisors, supported by intensive communication with parents. Consistent application of discipline has a positive impact on children's social development, evidenced by increased responsibility, independence, cooperation skills, adherence to rules, empathy, and improved social interaction. These findings confirm that cultivating discipline from an early age serves as an effective strategy for holistically supporting children's social development.